A compendium of contact force models inspired by Hunt and Crossley's cornerstone work. (January 2022) - Rodrigues da Silva, Mariana; Marques, Filipe; Tavares da Silva, Miguel; Flores, Paulo
Highlights: The Hunt and Crossley cornerstone work on the impact modeling is revisited. The main aspects of the dynamics of the collision between rigid bodies are addressed. Fifteen contact force models developed from the Hunt and Crossley model are compared. Abstract: The selection of the contact force model plays a crucial role in the modeling and analysis of dynamical systems. The seminal work by Hunt and Crossley, published in 1975, is one of the most prominent contact force models that finds application in different areas of science and engineering. The contact force approach proposed by Hunt and Crossley has motivated and inspired a large number of researchers that, eventually, led to the publication of numerous solutions to evaluate contact forces. This paper presents an extensive collection of contact force models available in the literature that have been developed on the basis of the Hunt and Crossley's cornerstone work. The behavior of each contact force model is assessed with a simple example of application and their performance is analyzed.